Seasonal dynamics of scrotal infrared profile and its relationship with seminal attributes of Murrah buffalo bulls - Ukey, Apeksha; Singh, Sohan Vir; Satpute, Tejeshwari; Singh, Pawan; Sharma, Roohani; Muhhamad NV, Afreed (Indian Journal of Dairy Science, 2025)
Research on relationship between infrared thermography (IRT) and semen quality, as well as the seasonal variation affecting and the documented reports on the influence of seasons on these relationships are scanty for Murrah bulls. Therefore, goal of experiment was to use Infrared thermography as a tool for evaluating seasonal influences on scrotal thermal profiles and its relationship with seminal traits in Murrah bulls (Bubalus bubalis).The study was conducted over year, encompassing five distinct seasons: hot dry, hot humid, autumn, winter and spring season, using eight healthy adult Murrah bulls. Environmental parameters were recorded to calculate Temperature Humidity Index (THI). Skin surface temperature at various anatomical sites (ear, eye, muzzle, forehead, flank and rump) along with scrotal surface temperature at distal pole, middle pole and proximal pole was recorded with the help of Infrared thermography. Semen ejaculates were collected using an Artificial Vagina (IMV Technologies, France). Skin surface temperature at different anatomical sites were significantly (p<0.05) lower during winter followed by spring, autumn, hot dry and hot humid seasons. A significantly (p<0.05) higher scrotal gradient was observed during winter compared to other season. Seminal parameters including ejaculate volume, sperm concentration, mass motility, progressive motility, viability, hypo-osmotic swelling test (HOST) and acrosomal integrity, were significantly (p<0.05) higher during autumn and spring season than other seasons. These findings highlight the importance of considering seasonal variation in scrotal gradient into account when creating breeding strategies. Optimizing these parameters can improve the semen quality and enhance reproductive efficiency of buffaloes.